Pearsonian archetypal analysis of Rin in R.F. Kuang's The Poppy War novel - Fryda Aulia Rahma; Maria Johana Ari Widayanti (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
Archetypes reflect the deep psychological complexity of a person's life journey. The phenomena can be exemplified by Rin, the main character in R.F. Kuang's novel The Poppy War. While previous research has explored the themes of gender and history, her psychological evolution through archetype transformation remains unexamined. This research addresses this gap by analysing Rin's character through Carol Pearson's twelve archetypes, revealing how trauma and ambition shape her reactions to certain situations. Using a descriptive qualitative approach, this study examines Rin's dialogue, actions, and thoughts. Findings identified five dominant archetypes in Rin's development which illustrate her psychological development from vulnerability to destructive empowerment. Those archetypes are The Orphan, The Warrior, The Seeker, The Destroyer, and The Magician. This study contributes to literary scholarship by demonstrating how archetype theory explains character psychology, offering a deeper understanding of narrative-driven identity formation in fiction.